PENGARUH EFIKASI DIRI, PENGETAHUAN MANAJEMEN KEUANGAN BISNIS, PENDIDIKAN KEWIRAUSAHAN, DAN LITERASI KEUANGAN TERHADAP INTENSI KEWIRAUSAHAAN - I Kadek Darmayasa; Ni Wayan Suartini; Ni Puru Yuli Tresna Dewi (Yayasan Nusantara Hasana Berdikari, 2024)
This research aims to analyze the influence of self-efficacy, business financial management knowledge, entrepreneurship education, and financial literacy on entrepreneurial intentions. The population of this study were all MSMEs in Klungkung Regency, Bali. The sampling technique used was the Slovis formula, with a total of 50 respondents. The data collection method was carried out using a Likert scale questionnaire. The analysis technique used is multiple linear regression analysis. The results of this study indicate that self-efficacy, entrepreneurship education, and financial literacy have no effect on entrepreneurial intentions. Knowledge of business financial management influences entrepreneurial intentions. Simultaneously, self-efficacy, business financial management knowledge, entrepreneurship education, and financial literacy influence entrepreneurial intentions.